2020
DOI: 10.3390/ijms22010219
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Translation Elongation Factor eIF5A Expression Is Regulated by Nutrient Availability through Different Signalling Pathways

Abstract: Translation elongation factor eIF5A binds to ribosomes to promote peptide bonds between problematic amino acids for the reaction like prolines. eIF5A is highly conserved and essential in eukaryotes, which usually contain two similar but differentially expressed paralogue genes. The human eIF5A-1 isoform is abundant and implicated in some cancer types; the eIF5A-2 isoform is absent in most cells but becomes overexpressed in many metastatic cancers. Several reports have connected eIF5A and mitochondria because i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 82 publications
(134 reference statements)
6
27
0
Order By: Relevance
“…Using yeasts that expressed the two yeast eIF5A analogs Tif51A and Tif51B Barba-aliaga et al [ 80 ] analysed how eIF5A expression is regulated to adapt yeast to the metabolic requirements. They observed that only the isoform Tif51A and not Tif51B, is needed for growth in the presence of glycerol and ethanol as carbon sources.…”
Section: Metabolismmentioning
confidence: 99%
“…Using yeasts that expressed the two yeast eIF5A analogs Tif51A and Tif51B Barba-aliaga et al [ 80 ] analysed how eIF5A expression is regulated to adapt yeast to the metabolic requirements. They observed that only the isoform Tif51A and not Tif51B, is needed for growth in the presence of glycerol and ethanol as carbon sources.…”
Section: Metabolismmentioning
confidence: 99%
“…Surprisingly, yeast lia1∆ mutants are viable, which suggests that the deoxyhypusinated form of eIF5A is partially functional in yeast, as has been demonstrated for at least some eIF5A functions [ 102 , 103 ]. In fact, only deoxyhypusine-eIF5A, but not hypusine-eIF5A, is found in yeast lia1∆ mutants, which indicates that the deoxyhypusine form can support growth [ 19 , 104 ]. Still, lia1∆ mutants are unable to form shmoos in the presence of the alpha-mating factor, suggesting that the complete hypusination process is necessary for some eIF5A-dependent functions [ 87 ].…”
Section: The Relevance Of Iron In Translation Elongationmentioning
confidence: 99%
“…Early studies centered on the influence of oxygen and heme levels over eIF5A expression, showing a reciprocal regulation where TIF51B mRNA levels increase in anaerobiosis, whereas TIF51A expression is up-regulated during aerobiosis [ 78 , 105 , 106 ]. More recent studies have shown that LIA1 mRNA levels also increase in anaerobiosis and that TIF51A , but not TIF51B , is required for growth under respiratory conditions, and its depletion reduces oxygen consumption [ 104 , 107 ]. Interestingly, full eIF5A hypusination is not required for maintaining high respiratory levels.…”
Section: The Relevance Of Iron In Translation Elongationmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that AteIF5A-3 has a more dominant role in nutrient and hormone translocation than in cell division [ 5 ]. In yeasts, Barba-Aliaga et al (2020) [ 74 ] described the different regulation activities of eIF5A isoforms during iron starvation, as eIF5A-1 was downregulated while eIF5A-2 was upregulated. Under Fe-deficient conditions, a generally decreased abundance of ribosomal proteins was investigated.…”
Section: Diverse Roles Of Eif5a Isoforms In Plantsmentioning
confidence: 99%